The relationship between theory of mind and executive functions in major depressive disorders: A review - Pagnoni, Ilaria; Gobbi, Elena; Alaimo, Cristina; Campana, Elena; Rossi, Roberta; Manenti, Rosa; Balconi, Michela; Cotelli, Maria (Frontiers in Psychiatry, 2022)
Patients suffering from Major Depressive Disorder (MDD) experience difficulties in multiple cognitive and affective abilities. A large body of literature has argued that MDD patients show impaired executive functions (EFs) and deficits in Theory of Mind (ToM), the ability to infer the mental states of others. However, the relationship between ToM and EFs has been poorly investigated. The aim of this review is to provide an overview of studies that evaluated the association between ToM and EFs in patients with MDD diagnosis. A literature review was conducted to identify all published studies in which ToM and EFs measures were administered to individuals with MDD and in which the relationship between these two domains was investigated. Eleven studies were included, and for each study, we discussed the findings related to ToM, EFs, and the nature of the link between these two aspects. Most of the studies reported that patients with MDD, compared with healthy controls, showed significant impairments in both ToM and EFs abilities. Moreover, this review indicates the presence of a significant association between these two domains in MDD patients, supporting the evidences that executive functioning is important to perform ToM tasks. Although the results that emerged are interesting, the relationship between ToM and EFs in MDD needs further investigation.